COMMUNITY EMPOWERMENT AND SUSTAINABLE TOURISM: THE IMPLEMENTATION OF COMMUNITY-BASED TOURISM PROGRAMME IN SONGKHLA CITY - Pratiwi, Briliani Putri Pijar; Kartina, Alessandro; Wardhana, Firnanda Hady; Hartono, Gita Alya; Inez Tasya Brilliant; Muhammad Ilham Arrasyid; Nabila Putri Siswandini; Naufal Izzuddin; Naura Khalilah Sandrina; Raisa Jawda Azzam (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
In the late years, Thailand is facing the increase of the tourist number per year. The numerous tourist took vacancy to the Thailand, has positive and also negative impact. Songkla is the city enriched with history and culture, face much challenges in their communities, including herbal product, fishery, and mini mango farm. This paper aim to analyse the role of community based tourism (CBT) concept to strenghtened local communities participation, to protect sustainability of tourism, and facing challenge that faced by local communites. Community based tourism concept emerged as the solution for local communities to balance the tourism development with local communities prosperity. Quantitative, with interview, field observation, and documentation has been done. The result shows that Mini Mango, seabass, and herbal product have big economy potency, but need much better quality control and storage-duration management. To solve those problems, government and local communities in Songkhla must collaborate altogether. When these industries keep developing, that will help local economy and preserve culture in Songkhla, Thailand.